Intracranial Aneurysms in Patients With Carotid Disease: Not So Rare As We Think. (January 2014) - Radak, Djordje; Sotirovic, Vuk; Tanaskovic, Slobodan; Isenovic, Esma R.
Before the routine use of computed tomography (CT) angiography, decisions for carotid artery treatment were mostly based on ultrasound findings and conventional angiography. Implementation and increasing use of CT angiography provided better visualization of the carotid and vertebrobasilar arteries system leading to an unexpected more frequent detection of unruptured intracranial aneurysms (UIAs). Concomitant presence of intracranial aneurysms in patients with severe carotid stenosis is a potential cause of significant mortality and morbidity. Due to the possible higher risk of aneurysm rupture after carotid procedures and ischemic events after aneurysm repair, the simultaneous presence of both lesions creates several therapeutic dilemmas. We review the prevalence of UIAs in patients with carotid occlusive disease and management difficulties and the current treatment strategies for handling the concomitant presence of these life-threatening diseases.